Sperm morphology of Elasmus polistis Burks, 1971 (Hymenoptera: Chalcidoidea: Eulophidae). (December 2019) - Nere, Pedro; Dias, Glenda; Santos, Helen P.; De Souza, André; Lino-Neto, José
Highlights: The sperm morphometry distinguishes E. polistis from the other Chalcidoidea studied. The nucleus-flagellum transition can be used to distinguish chalcidoid families. The E. polistis sperm showed two central microtubules within the basal body. Abstract: The sperm morphology of the parasitoid Elasmus polistis (Eulophidae) has been investigated with light and transmission electron microscopy. The sperm were filiform and spiraled, with 165.6 (± 4.6) μm in length, and showed a distinctive head, formed by a one-layered small acrosome and a nucleus, and a flagellar region. An extracellular sheath from which many long filaments radiated out covered the acrosome and part of the nucleus. The spiral nucleus, with 24.1 (± 1.3) μm in length, was filled with homogeneously compact chromatin. In the nucleus-flagellum transition, the centriole adjunct extended posteriorly from the nuclear base in a spiral around the basal body, which has two central microtubules, and axoneme for approximately 1.1 μm. The two mitochondrial derivatives began roughly at the same level and at the base of the centriole adjunct. In cross-section, they were symmetrical, with a slightly oval shape and a smaller diameter in comparison to the axoneme. The latter, also spiraled, consisted of 9 + 9 + 2 microtubules that was formed from the basal body situated just below and aligned with the nucleus. The E. polistis sperm showed the same basic structures and morphological characteristics as observed in other Chalcidoidea. However, it was possible to distinguish the sperm of this species from those of other Eulophidae by (i) the long length of the centriole adjunct on the flagellum, and (ii) the presence of two central microtubules within the basal body. The sperm characteristics suggest that Eulophidae is closely related to Trichogrammatidae and both families are more similar to Eurytomidae, Pteromalidae, and Torymidae than Agaonidae.